The Global Impact of the Gynecologic Cancer InterGroup in Enhancing Clinical Trials in Ovarian Cancer. Issue 4 (1st April 2011) - Bacon, Monica; Kitchener, Henry; Stuart, Gavin C.E.; Vermorken, Jan B.
Abstract : The Gynecologic Cancer InterGroup (GCIG) has developed from a small network of ovarian cancer researchers to a large international forum addressing multiple issues related to research in gynecologic cancers. Member groups of the GCIG have collaboratively conducted pivotal clinical trials in cancers of the ovary, endometrium, and cervix. The participation of operational and statistical personnel from the GCIG member groups has facilitated a collegial approach to international differences and restrictions. One of the powerful initiatives of the GCIG is the facilitation of the Ovarian Cancer Consensus Conference every few years. The 4th Ovarian Cancer Consensus Conference was held in Vancouver, Canada, in June 2010, and the resulting publications (herein) provide an invaluable resource to researchers in the field of gynecologic oncology.